Flatness-based adaptive nonlinear control for torque tracking of electro-hydraulic friction load simulator with uncertainties. (September 2019) - Jing, Chenghu; Xu, Hongguang; Jiang, Jihai
Electro-hydraulic friction load simulator is able to simulate load for detecting and estimating the actuator system, which requires an ability to track accurately a given signal with high frequency. In this article, a flatness-based adaptive nonlinear controller is proposed for electro-hydraulic friction load simulator with parameter uncertainties to improve torque-tracking performance. The proposed control consists of state feedback, desired input feedforward and adaptive law to yield a stable closed-loop control system. State feedback is designed to stabilize the electro-hydraulic friction load simulator and achieve robustness against disturbances. Desired input feedforward is designed based on flatness property. And, it can enhance bandwidth by model compensation. Furthermore, in order to solve the problem of parameter uncertainty, adaptive law is adopted in this controller. The proposed controller theoretically guarantees asymptotic tracking performance in the absence of parameter uncertainties. High-accuracy tracking performance of the proposed control strategy is verified by experiments.